Asymmetric cost and benefit perceptions in willingness‐to‐donate decisions. (27th November 2019) - Rubaltelli, Enrico; Hysenbelli, Dorina; Dickert, Stephan; Mayorga, Marcus; Slovic, Paul
Abstract: Charitable giving entails the act of foregoing personal resources in order to improve the conditions of other people. In the present paper, we systematically examine two dimensions integral to donation decisions that have thus far received relatively little attention but can explain charitable behavior rather well: the perceptions of cost for the donor and benefit for the recipients. In line with current theories in judgment and decision making, we hypothesize that people weigh these dimensions subjectively and perceive them asymmetrically, consistent with prospect theory. Costs for the donor are typically perceived as losses, whereas benefits for recipients are perceived as gains. In four studies, we presented several scenarios to participants in which both donation amounts (costs) and number of lives helped (benefits) were manipulated while keeping the ratio of costs and benefits constant. Results from Studies 1 and 2 showed that willingness to help decreased as donation amounts and number of lives helped increased. Additionally, Studies 3 and 4 provide evidence for a solution to reduce the asymmetry and increase donation amounts as the number of lives at risk increases.